Diabetic Foot Self Care Pada Diabetisi - Defrima Oka Surya; Zulham Efendi; Afrizal Afrizal; Ria Desnita (Malahayati Nursing Journal, 2022)
ABSTRACT: DIABETIC FOOT SELF CARE ON DIABETES PATIENTS Background: Diabetes Mellitus (DM) can cause complications in various body systems. One of the complications of DM is complications in the feet which can cause diabetic foot ulcers and lead to leg amputation. Diabetic foot complications can be prevented by performing routine foot care or diabetic foot care. Objective: The purpose of this study was to determine the description of diabetic foot care in patients with diabetes mellitus consisting of personal self-care, podiatric care, and footwear and socks. Method: This type of research is descriptive quantitative research. Data was collected using a diabetic foot care questionnaire. The number of samples in this study was 51 people. The sampling method is a non-probability technique using consecutive sampling. The study was conducted in the Kuranji Health Center Working Area in July – November 2021. Result: The results showed that most respondents (64.70%) had poor personal self-care in foot care, 82.3% of respondents had poor podiatric care habits. and 52.94% of respondents have good habits in choosing footwear. Conclusion: From the results of the study, it was concluded that people with diabetes have bad habits in performing foot care so that this is one of the risk factors for complications in the feet. To increase awareness of people with diabetes in performing foot care, it is recommended that nurses can provide education and teach people with diabetes to take care of their feet Keywords: Diabetes Mellitus; Foot Complications; Foot Care  INTISARI : DIABETIC FOOT SELF CARE PADA DIABETISI Latar Belakang : Diabetes Melitus (DM) dapat menyebabkan komplikasi pada berbagai sistem tubuh. Salah satu komplikasi DM adalah komplikasi pada kaki yang dapat menimbulkan ulkus kaki diabetik dan berujung dengan amputasi kaki. Pencegahan komplikasi pada kaki dapat dilakukan diabetisi dengan melakukan perawatan kaki rutin atau diabetic foot care.Tujuan : Tujuan penelitian ini adalah untuk mengetahui gambaran diabetic foot care pada pasien diabetes melitus yang terdiri dari personal self care, podiatric care, serta footwear and sock.Metode : Jenis penelitian ini adalah penelitian deskriptif kuantitatif. Pengumpulan data dilakukan menggunakan kuesioner diabetic foot care. Jumlah sampel dalam penelitian ini adalah 51 orang. Metode pengambilan sampel adalah dengan Teknik non probability dengan menggunakan consecutive sampling. Penelitian dilakukan di Wilayah Kerja Puskesmas Kuranji pada Bulan Juli – November 2021.Hasil : Hasil penelitian menunjukkan bahwa sebagian besar responden (64,70%) memiliki personal self care yang kurang baik dalam perawatan kaki, 82,3% responden memiliki kebiasan podiatric care yang kurang baik dan 52,94% responden memiliki kebiasaan baik dalam pemilihan alas kaki.Kesimpulan : Diabetisi memiliki kebiasaan yang kurang baik dalam melakukan perawatan kaki sehingga ini menjadi salah satu faktor resiko terjadinya komplikasi pada kaki. Untuk meningkatkan kesadaran diabetisi dalam melakukan perawatan kaki disarankan perawat dapat memberikan edukasi dan mengajarkan diabetisi untuk melakukan perawatan kaki Kata Kunci : Diabetes Melitus; Komplikasi Kaki; Perawatan Kaki